49 Review of potential geographical disparities in access to anti-fibrotic medication and clinic-based specialist palliative care for patients with idiopathic pulmonary fibrosis. (13th October 2019) - Wakefield, Kym; Palmer, Evelyn; Donaldson, Claire; Bourke, Anne-Marie; Forrest, Ian
Abstract : Background: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease of unknown origin (NICE, 2013). Disease-modifying anti-fibrotics are restricted to patients who meet specific criteria and are prescribed by regional IPF centres (NICE, 2016; NICE, 2018). Patients should be offered best supportive care from diagnosis (NICE, 2013). In January 2016 specialist palliative care (SPC) support was embedded in a regional IPF clinic. Initial service review (Kavanagh, 2017) suggested potential geographical disparities in access to both anti fibrotics and clinic-based SPC. Aim: To repeat the 2016 review to assess whether geographical disparities have changed over time. Methods: The sex, age and postcode of all patients with known IPF prescribed anti-fibrotics or seen by clinic-based SPC between January 2016 and April 2019 were collected retrospectively and geographically plotted. Chi squared goodness of fit was used to calculate statistical significance. Results: 398 patients were started on anti-fibrotics (male:female 330:68, mean age 74.7). Geographical plotting shows significant variation by region (P<0.01) ranging from 6.1 to 16.2 per 100, 000 population, with comparatively low numbers of patients from Cumbria and North Durham (See figure 1 ). 80 patients were seen by SPC (male:female 65:15, mean age 74.9). Again, geographical plotting shows significant variation by region (P<0.02) ranging from 0.9 to 4.5 per 100, 000 population, with a higher proportion of patients from Newcastle-Gateshead (See figure 2 ). Discussion: Geographical distribution of patients seen by clinic-based SPC appears to have changed little since 2016, with clear centralisation to Newcastle-Gateshead. Speculatively, reasons for this could include travel distances and local palliative care provision. Geographical disparity in antifibrotic prescription is more difficult to account for and requires further investigation. References: National Institute for Health Care and Excellence (NICE). (2013) Idiopathic Pulmonary Fibrosis in Adults (CG163) [online]. https://www.nice.org.uk/guidance/cg163. Accessed 04/07/2019. National Institute for Health Care and Excellence (NICE). (2016) Nintedanib for Treating Idiopathic Pulmonary Fibrosis (Technology Appraisal Guidance TA379) [online]. https://www.nice.org.uk/guidance/ta379. Accessed 04/07/2019. National Institute for Health Care and Excellence (NICE). (2018) Pirfenidone for Treating Idiopathic Pulmonary Fibrosis (Technology Appraisal Guidance TA504) [online]. https://www.nice.org.uk/guidance/ta504/chapter/1-Recommendations. Accessed 04/07/2019. Kavanagh E, et al . Integration of specialist palliative care into a tertiary non-malignant service: evaluation of potential geographical disparity. BMJ Supportive & Palliative Care 2017;7 (Suppl 1):A33–A34.